Novel method for setting up 3D navigation system with skin-fixed dynamic reference frame in anterior cervical surgery. (2nd January 2015) - Jang, Sang Hoon; Cho, Ji Young; Choi, Won chul; Lee, Ho Yeon; Lee, Sang-Ho; Hong, Jae Taek
Abstract: Purpose : To introduce easy and useful methods using 3D navigation system with skin-fixed dynamic reference frame (DRF) in anterior cervical surgery and to validate its accuracy. Methods : From September 2012 to May 2013, 31 patients underwent anterior cervical surgery and a total of 48 caspar distraction pins were inserted into each cervical vertebra. Every operation was performed using O-arm® navigation system with skin-fixed DRF. To validate the accuracy of these methods, a custom-made metal sleeve was used. In surgical field, through the metal sleeve, the tip of a navigation probe promptly contacts to the tip of caspar pin. We measured the vertical and horizontal distances and the angular deviation in sagittal plane between the caspar pin and the navigation probe on the virtual images and evaluated accuracy of navigation system with skin fixed DRF. Results : Total 31 (males 20, females 11) patients and 48 caspar pins were included in this study. The mean horizontal distance between the caspar pin and the navigation probe displayed in navigation monitor was 0.49 ± 0.71 mm. The mean vertical distance between the caspar pin and the navigation probe displayed in navigation monitor was 0.88 ± 0.93 mm. And the mean angular deviation in sagittal plane between the caspar pin and the navigation probe displayed in navigation monitor was 0.59 ± 0.55°. Conclusions : 3D navigation system with skin-fixed DRF in anterior cervical surgery is a simple and reliable method and it can be a helpful supplement to a spine surgeon's judgement.